2019
DOI: 10.3758/s13423-019-01620-x
|View full text |Cite
|
Sign up to set email alerts
|

Slow naming of pictures facilitates memory for their names

Abstract: Speakers remember their own utterances better than those of their interlocutors, suggesting that language production is beneficial to memory. This may be partly explained by a generation effect: The act of generating a word is known to lead to a memory advantage (Slamecka & Graf, 1978). In earlier work, we showed a generation effect for recognition of images (Zormpa, Brehm, Hoedemaker, & Meyer, 2019). Here, we tested whether the recognition of their names would also benefit from name generation. Testing whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This modification of the basic equations of ACT‐R would require thorough testing using data from properly powered experimental designs. Such data do not exist yet, so such a large‐scale evaluation is not currently possible; however, more and more researchers are attending to the power properties of their studies (Brehm & Goldrick, 2017; Stack, James, & Watson, 2018; Zormpa, Meyer, & Brehm, 2019), and we expect that such data will become available in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This modification of the basic equations of ACT‐R would require thorough testing using data from properly powered experimental designs. Such data do not exist yet, so such a large‐scale evaluation is not currently possible; however, more and more researchers are attending to the power properties of their studies (Brehm & Goldrick, 2017; Stack, James, & Watson, 2018; Zormpa, Meyer, & Brehm, 2019), and we expect that such data will become available in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is attributable to a combination of two established effects in the memory for language literature. Generating labels for items, rather than reading or hearing them, creates a memory benefit known as the generation effect (Bertsch et al, 2007; Dew & Mulligan, 2008; Slamecka & Graf, 1978; Zormpa, Brehm, et al, 2019; Zormpa, Meyer, et al, 2019), while producing words aloud, rather than saying them silently, creates a memory benefit known as the production effect (MacLeod et al, 2010; Ozubko et al, 2014; Zormpa, Brehm, et al, 2019). In the elicited conversations in Experiment 3, individuals had to generate as well as produce their responses, enhancing memory due to both effects.…”
Section: Discussionmentioning
confidence: 99%
“…Psychologists (Cohen 1962(Cohen , 1988 have long pointed out the importance of ensuring high statistical power for making discovery claims, but until recently these recommendations have largely been ignored in linguistics, psychology, and psycholinguistics; some recent papers that take power into account are Brehm and Goldrick (2017); Stack et al (2018); Zormpa et al (2019). In response to the replication crisis that (partly) resulted from underpowered studies (Open Science Collaboration 2015), several remedies have been suggested, such as reducing the probability of committing a Type I error to 0.005 (Benjamin et al 2018), or abolishing statistical significance testing entirely (McShane et al 2019).…”
Section: Some Problems With Significance Testingmentioning
confidence: 99%